2014
DOI: 10.1007/s00705-014-2033-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a recombinant-glycoprotein-based latex agglutination test for rabies virus antibody assessment

Abstract: The measurement of neutralizing antibodies induced by the glycoprotein of rabies virus is indispensable for assessing the level of neutralizing antibodies in animals or humans. A rapid fluorescent focus inhibition test (RFFIT) has been approved by WHO and is the most widely used method to measure the virus-neutralizing antibody content in serum, but a rapid test system would be of great value to screen large numbers of serum samples. To develop and evaluate a latex agglutination test (LAT) for measuring rabies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A percentage of 97% of monoclonal antibodies recognize antigenic sites [15]. Rabies virus antigenic sites play an important role in the disease pathogenies [16,17,18]. In addition, it is discovered that to sustain viral pathogenicity, the expression of viral proteins and conservancy of many viral elements must be maintained [18], especially G protein must be controlled.…”
Section: Rabies Virus Antigenic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A percentage of 97% of monoclonal antibodies recognize antigenic sites [15]. Rabies virus antigenic sites play an important role in the disease pathogenies [16,17,18]. In addition, it is discovered that to sustain viral pathogenicity, the expression of viral proteins and conservancy of many viral elements must be maintained [18], especially G protein must be controlled.…”
Section: Rabies Virus Antigenic Structurementioning
confidence: 99%
“…About twenty-four thousand die due to rabies in Africa annually and dogs are the main reason for infection transmission [1]. Fortunately, it is a vaccine-preventable disease [4] and the most important way to prevent is vaccination of both pets and people [16]. The rabies vaccine is a type of inactivated virus vaccine that is prepared either in human diploid cell culture [HDCV] or in purified chick embryo cell culture [PCEC] [5].…”
Section: Introductionmentioning
confidence: 99%
“…During infection and vaccination, the glycoprotein plays a major role as an antigenic stimulant and induces neutralizing antibodies (Jemima et al, 2014). Several studies have confirmed that glycoprotein gives protection against rabies.…”
Section: Rabies Virus Glycoprotein (Rvg) -Importance In Protecting Anmentioning
confidence: 99%
“…2014 A rapid field test latex agglutination test (LAT) was developed for measuring RABV antibodies using recombinant glycoprotein expressed in an insect cell system. Jemima et al (2014) 14. 2014…”
mentioning
confidence: 99%